Autoimmune thyroiditis in patients with sudden sensorineural hearing loss. Issue 2 (10th February 2022) - Sun, Xiao‐Mei; Zhuang, Shi‐Min; Xiao, Zhi‐Wen; Luo, Jia‐Qi; Long, Zhen; Lan, Lin‐Chan; Zhang, Hui‐Qing; Zhang, Guan‐Ping
Abstract: Objective: This study aims to evaluate the association between autoimmune thyroiditis and Sudden Sensorineural Hearing Loss (SSNHL). Methods: Hundred and five patients with SSNHL were enrolled. Audiometric tests, serum thyroid autoantibodies (TPOAb, TgAb) were studied. Based on the thyroid autoantibody results, patients were divided into two groups: thyroid autoantibody‐positive and negative. The relationship between thyroid autoimmunity and audiological characteristics was analyzed. Results: Twenty‐six patients (24.8%) of the SSNHL had thyroid autoantibody elevated. The pure tone average (PTA) of patients with and without thyroid autoantibody is 60 ± 38.51 and 54.99 ± 33.87 dBHL, respectively. The PTA was significantly improved in both groups after treatment ( p < 0.001), but the hearing gains were similar in both groups ( p = 0.205). Hearing loss of 2000–8000 Hz was worse than 125–1000 Hz among thyroid autoantibody‐positive patients ( p < 0.05), but the hearing improvement of both groups have no significant difference. The hearing improvement of 125–1000 Hz is significantly better than 2000–8000 Hz among patients with thyroid autoantibody negative ( p < 0.05). Conclusions: We speculate that a potential association between thyroid autoimmunity and SSNHL. Thyroid autoimmunity may be a pathogenesis factor of SSNHL and associated with more severe hearing loss of high‐frequency hearing. Abstract : The study evaluated the association between autoimmune thyroiditis and Sudden Sensorineural Hearing Loss (SSNHL). We speculate that a potential association between thyroid autoimmunity and sudden sensorineural hearing loss. Patients with SSNHL have unique clinical audiological characteristics. Thyroid autoimmunity may be a pathogenesis factor of SSNHL and be associated with more severe hearing loss of high‐frequency hearing.